Your brain is always listening : tame the hidden dragons that control your happiness, habits, and hang-ups - Amen, Daniel G. (Tyndale Momentum, the Tyndale nonfiction imprint, 2021)
"New York Times bestselling author Dr. Daniel Amen equips you with powerful weapons to battle the inner dragons that are breathing fire on your brain, driving unhealthy behaviors, and robbing you of joy and contentment. Your brain is always listening and responding to these hidden influences and unless you recognize and deal with them, they can steal your happiness, spoil your relationships, and sabotage your health. This book will teach you to tame the: 1. Dragons from the Past that ignite your most painful emotions; 2. Negative Thought Dragons that attack you, fueling anxiety and depression; 3. They and Them Dragons, people in your life whose own dragons do battle with yours; 4. Bad Habit Dragons that increase the chances you'll be overweight, overwhelmed, and an underachiever; 5. Addicted Dragons that make you lose control of your health, wealth, and relationships; 6. Scheming Dragons, advertisers and social media sites that steal your attention. In Your Brain Is Always Listening, Dr. Daniel Amen shows you how to recognize harmful dragons and gives you the weapons to vanquish them. With these practical tools, you can stop feeling sad, mad, nervous, or out of control and start being happier, calmer, and more in control of your own destiny"--